ANALYZING FORESHADOWING IN A NOVEL: THE EXAMPLE OF OF MICE AND MEN BY JOHN STEINBECK (Modern education and development, 2024)
One important literary technique authors employ to set readers up for future events in a story is foreshadowing. John Steinbeck employs foreshadowing in Of Mice and Men to create tension and emotional depth while obliquely implying the tragedies that the characters will inevitably face. By incorporating foreshadowing into the narrative through symbolic components, dialogues, and significant occurrences, Steinbeck reflects on the story's main themes of friendship, loneliness, and dashed hopes. This article explores significant foreshadowing moments in the novella and considers how they contribute to the work's increased effect on readers.